ANALISA PENGARUH FAKTOR PENDIDIKAN TERHADAP PARTISIPASI POLITIK PEREMPUAN PADA PEMILIHAN KEPALA DESA (PILWU) TAHUN 2017 DI KECAMATAN WIDASARI - Syukron Ma'mun (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2018)
Background of this reaserch is the low of women participation in various agenda of general election in level national, province, or local. This reaserch amin to know the influence of level of education to woman political participation in election of Village head 2017 in Widasari District. The research approch in this reaserch is qualitatif approach with case study methode. Subyect in this reserah is woman candidats from three villages in Widasari District which perform the election of village head. From four villages which perform village head election, there is three villages with woman candidat of village head which is Kongsijaya Village, ujung jaya Village, and Leuwigede Village. The reaserch instrumen use in this reaserch is observation sheet and interview sheet to woman candidat of village head. The result of this reaserch is proof that education is not main determinant of women participation to nominate as village head. There is other factor that influence women participation in village head election in Widasari distric 2017 which is husband support and experience un social organization.